THE INFLUENCE OF MOTIVATION AND PHYSICAL WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT CV. PUTRA ABADI JAYA, TANGERANG REGENCY - Iis Noviyanti; Lia Asmalah; Juwita Ramadani Fitria (International Journal Management and Economic, 2025)
This study aims to analyze the impact of motivation and the physical work environment on employee performance at CV. Putra Abadi Jaya, Tangerang Regency. The research method uses a quantitative approach with data collection through questionnaires from 65 employees. The motivation variable includes physiological needs, security, self-esteem, and self-actualization, while the physical work environment covers lighting, ventilation, workspace comfort, and cleanliness. Employee performance is measured through work quality, productivity, and time discipline. The analysis results show that motivation significantly affects employee performance. The physical work environment also significantly impacts employee performance. Simultaneously, both variables together have an impact on employee performance, with an F-value of 74.292 and an R² of 0.706, indicating that 70.6% of the variation in employee performance is explained by motivation and the physical work environment. This study concludes that increasing motivation and improving the physical work environment can significantly enhance employee performance. CV. Putra Abadi Jaya is recommended to continue optimizing motivation factors and the physical work environment to support employee productivity and well-being.